Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/mpa.0000000000001460
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Endoscopic Ultrasound-Guided Fine-Needle Aspiration for Pancreatic Solid Pseudopapillary Neoplasm Before Surgical Resection

Abstract: Objectives The results of only a few endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) for pancreatic solid pseudopapillary neoplasm (SPN) have been published, and the safety of the procedure has never been investigated. Our study compared the recurrence rate in patients with and without preoperative EUS-FNA. Methods This European multicenter registry-based study was conducted in 22 digestive units, and retrospectively included all patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…The application of endoscopic ultrasound (EUS) maybe a better solution. Preoperative EUS and EUS guided tissue acquisition allowed pancreatic SPN diagnosis in 80%-90 cases (24,25). Moreover, the Ki67 index can be measured by the specimens obtained by EUS guided tissue biopsy (26).…”
Section: Discussionmentioning
confidence: 99%
“…The application of endoscopic ultrasound (EUS) maybe a better solution. Preoperative EUS and EUS guided tissue acquisition allowed pancreatic SPN diagnosis in 80%-90 cases (24,25). Moreover, the Ki67 index can be measured by the specimens obtained by EUS guided tissue biopsy (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, although SPNs often contain cystic components, EUS-FNA for cystic tumors is controversial in terms of safety. A multicenter study of FNA procedures in Europe by Karsenti et al [ 16 ] that evaluated the risk of tumor dissemination suggested that there was no recurrence or dissemination after surgery. On the other hand, Yamaguchi et al [ 17 ] reported the world’s first case of dissemination after EUS-FNA for SPN.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, older age is an independent risk factor for recurrence[ 21 ] and is significantly associated with tumor recurrence[ 22 ]. In addition, as there are no significant differences in margin status, peripheral tissue invasion, postoperative complications, disease-free survival, or overall survival between male and female patients, the prognosis of SPNs has been reported to be similar between male and female patients[ 21 ].…”
Section: Precautions Of and Relevant Suggestions For Enucleation Appl...mentioning
confidence: 99%